Changes in the epipelic diatom assemblage in nutrient rich streams due to the variations of simultaneous stressors - Cochero, Joaquin (2015)
Benthic diatoms are often used for assessing environmental conditions, such as water quality and habitat conditions in stream and river systems. Although laboratory experiments have shown that each diatom species have different levels of tolerance to different stressors, few studies have been conducted in laboratory settings that analyze the responses of the diatom assemblage to the effects of multiple simultaneous variables. The aim of this study was to evaluate some structural responses (such as species composition and diversity) of the diatom assemblage on a short time scale to the effects of the simultaneous increase in four variables that are directly linked to the environmental changes affecting the Pampean streams: turbidity, nutrients (phosphorous and nitrogen), water velocity and temperature. To this end we conducted a five-week laboratory experiment using artificial channels where we simulated two environmental conditions (LOW and HIGH) employing epipelic biofilm from a mesotrophic stream. The results obtained in the experiment show that the structure of the diatom assemblage in the epipelic biofilm is affected by the simultaneous modification of temperature, water velocity, nutrient concentration and turbidity. These modifications in the assemblage included moderate decreases in diversity, small decreases in the proportion of species sensitive to eutrophication and saprobity, moderate increases in the IDP (Pampean Diatom Index) values and moderate changes in the percentages of the stalked growth-forms. The relative abundance of species such as Luticola mutica, Navicula cryptocephala and Navicula lanceolata were negatively affected by both treatments; other species such as Planothidium lanceolatum, Caloneis bacillum, Encyonema minutum, Humidophila contenta, Luticola kotschyi, Nitzschia amphibia, Navicula veneta, Pinnularia subcapitata var. subcapitata were positively affected by the HIGH treatment; and Nitzschia fonticola was positively affected by both treatments. The results suggest that, in the very short term of the bioassay conducted, the diatom assemblage can modify its structure to respond in a sensitive manner to the abrupt changes in multiple physical-chemical variables.